An unexpected new species of Anomala Samouelle, 1819 from southern Italy (Coleoptera: Scarabaeidae: Rutelinae), including description of its larva and ecological notes - Uliana, Marco; Tomasi, Filippo; Gallerati, Valerio (Zootaxa, 2023)
Anomala phantasma Uliana, Tomasi & Gallerati, new species is described from the Salento peninsula, southern Italy, including its third-instar larva. The new species is close to Anomala devota (P. Rossi, 1790), from which it differs for characters of the external anatomy, of the paramera and the endophallus. The most striking diagnostic difference is found in the setation of pronotum, limited to a narrow stripe on the midline in A. phantasma, new species, whereas it is present on the whole surface in A. devota. The new species is also compared with A. matzenaueri Reitter, 1918, a poorly known species endemic of the opposite side of the Adriatic coast. Anomala phantasma, new species is a day-active species, possibly limited to maquis and shrublands lining sandy beaches.